The association between the site of back pain and number of painful sites with daily activities, seeking healthcare, and medication use among school adolescents - Tatiana Rehder Gonçalves; Tatiana Rehder Gonçalves; Mauro Felippe Felix Mediano; Rosely Sichieri; Diana Barbosa Cunha (Frontiers in Pain Research)
IntroductionThe potential consequences of back pain (BP) are poorly described in adolescents. This study evaluated the association between BP sites (neck, thoracic and low back) and number of painful sites with missed school classes, interference in physical activities, seeking healthcare, and medication use among school adolescents.MethodsThis cross-sectional study included 350 students (5th to 9th grade) of a public school in Brazil. Information on BP site and outcomes were self-reported. Logistic regression analyses were performed.ResultsParticipants reporting at least one painful site in spine were 74.9% (n = 262), with mean age of 12.73 ± 1.67 (55.7% were girls). Most of them reported pain in two sites (n = 100; 28.6%) and the most frequent pain site was neck (n = 223; 63.7%). Thoracic and low BP were associated with missing school classes, interference in physical activities, seeking healthcare, and medication use, while neck pain showed no association. The number of painful sites was associated with daily activities and healthcare with those gradients increasing with the number of painful sites.ConclusionThoracic and low BP were associated with daily activities, seeking healthcare, and medication use in early adolescence.